Cathedral antiquities Historical and descriptive accounts with 311 illustrations, of the following English cathedrals : Viz. Canterbury, York, Salisbury, Norwich, Oxford, Winchester, Lichfield, Hereford, Wells, Exeter, Worcester, Peterborough, Gloucester, and Bristol - Britton, John 1771-1857; Princeton Theological Seminary (London M.A. Nattali, 1836)
V. 1. Canterbury and York -- V. 2. Salisbury, Norwich, and Oxford -- V. 3. Winchester, Lichfield, and Hereford -- V. 4. Wells, Exeter, and Worcester -- V. 5. Peterborough, Gloucester, and Bristol.
Each volume has also special and engraved title-pages
Keywords: Cathedrals -- England; Church Architecture -- England; Fine Arts